Kesepakatan ASEAN dalam Menangani Kebakaran Hutan dan Lahan Indonesia, 1990-2015 - Hamdani, Muhammad Fachrizal; Rohmawati, Yulia; Nurhidayati, Reni Putri (Universitas Gadjah Mada, 2024)
Indonesia is a country that experiences many cases of forest and land fires, so this has triggered ASEAN to take the initiative to resolve the problem through two agreements, namely the 1997 Regional Haze Action Plan (RHAP) and the ASEAN Agreement on Transboundary Haze Pollution (AATHP) which was ratified by all ASEAN members. 2014. Therefore, this research focuses on Malaysia's and Singapore's responses to Indonesia in handling Indonesia's forest and land fire cases through the RHAP and AATHP from 1990 to 2015, as well as the impact of these two ASEAN policies on Indonesia in addressing forest and land fires. This research method is a historical research method using laws, written regulations, newspapers, articles, and books as research sources. The research results indicate that Malaysia's and Singapore's responses to Indonesia within the RHAP framework were effective because each country had its own focused tasks. Indonesia experienced positive impacts from the RHAP policy because the three countries took direct actions in addressing forest and land fires in Indonesia. Conversely, Malaysia's and Singapore's responses to Indonesia within the AATHP framework were less effective due to their persistent pressure on Indonesia to ratify the AATHP quickly. Indonesia experienced more negative impacts from the AATHP policy because it received a negative image from Malaysia and Singapore due to the prolonged AATHP ratification process.